2019
DOI: 10.1148/rg.2019180097
|View full text |Cite
|
Sign up to set email alerts
|

Primary and Secondary Breast Lymphoma: Clinical, Pathologic, and Multimodality Imaging Review

Abstract: Breast lymphoma is a rare hematologic neoplasm that originates in the breast lymphoid tissue and includes primary breast lymphoma (PBL) and secondary breast lymphoma (SBL). PBL involves the breast lymphoid tissue in the absence of previously identified extra mammary lymphoma and widespread disease. SBL is the most common metastasis to the breast, accounting for 17% of metastatic disease to the breast. PBL and SBL usually demonstrate imaging phenotypes that overlap with those of primary breast carcinoma, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
136
1
14

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(157 citation statements)
references
References 71 publications
6
136
1
14
Order By: Relevance
“…3 The commonest histological subtype is diffuse large B-cell type (DLBCL), and the age of incidence is between 9 and 85 years with median age range between 55 and 65 years. 4,7 Our patient was 18 years old which is in the age range but with huge gap from median age. There was a delay of over a year in the establishment of the final diagnosis.…”
Section: Discussionmentioning
confidence: 86%
“…3 The commonest histological subtype is diffuse large B-cell type (DLBCL), and the age of incidence is between 9 and 85 years with median age range between 55 and 65 years. 4,7 Our patient was 18 years old which is in the age range but with huge gap from median age. There was a delay of over a year in the establishment of the final diagnosis.…”
Section: Discussionmentioning
confidence: 86%
“…The typical clinical presentation of PBL is with a solitary breast lump in female patients between 50 and 70 years of age [ 1 , 8 ]. Similarly, 39% of the patients presented with a breast lump, and the median age of the patients was 66 years in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Mammographic features of PBL are distinct from invasive breast cancer. The role of breast ultrasound and magnetic resonance imaging in PBL diagnosis is not well established yet [ 7 - 8 , 13 ]. Retrospective studies reported no benefit of radical mastectomy compared to partial mastectomy or biopsy in terms of overall survival (OS) and progression-free survival (PFS) rates.…”
Section: Introductionmentioning
confidence: 99%
“…Although imaging studies in cases of breast lymphoma can suggest malignancy, they are not helpful in differentiating lymphoma from carcinoma. Therefore, accurate diagnosis is based on biopsy [19].…”
Section: Discussionmentioning
confidence: 99%